The value of information in supply chain decisions: A review of the literature and research agenda. (June 2018) - Viet, Nguyen Quoc; Behdani, Behzad; Bloemhof, Jacqueline
Highlights: A structured review on value of information in supply chain decisions literature published between 2006 and 2017. A rigorous review framework of four dimensions: supply chain decisions, information, modelling approach, and context. A structured agenda for future research on value of information in supply chain decisions. A stepwise framework as guidance to assess value of information in supply chain decisions. Abstract: The purpose of this paper is to provide a structured overview of the value of information in different supply chain decisions and to identify a research agenda based on the current state of research on the topic. The paper uses the systematic literature review methodology to review journal articles published in the 12-year period from 2006 to 2017. Each selected study is analyzed using a rigorous review framework of four primary dimensions, including "supply chain decisions", "information", "modelling approach", and "context". The review of articles shows that the current literature is rich in assessing the value of information in inventory decisions, yet insufficient in other supply chain areas such as facility, transportation, sourcing, and pricing. In addition, the value of information is subject to contextual supply chain parameters and varies in accordance with the characteristics of the information (such as accuracy, timeliness, and completeness). Furthermore, the focus of the existing literature is on "information availability" in supply chain decisions, and the impact of important information characteristics on the value of information has not been studied extensively. The research on information timeliness and its influence on supply chain performance is especially limited. Based on the discussion and results of our review, a research agenda is offered and sample research questions are discussed.